2018
DOI: 10.1063/1.5061890
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coral reef conservation education on students’ social sensitivity (A co-curricular learning experimental study at SMKN 61 Jakarta Pulo Tidung Besar Regency, Kepulauan Seribu)

Abstract: The use of the coral reef as a source of community livelihood on Tidung Besar Island has negative impacts on the coral reef itself. Students of SMKN 61 Jakarta are a small part of the Tidung Besar community that is involved in coral reef conservation efforts on Tidung Besar Island. Efforts to build social sensitivity can be conducted at schools through co-curricular education activities. Co-curricular activites are activities to add to, supplement or replace intracurricular learning, which is according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…Another study by Puspitaningrum et al (2018) concluded that coral reef conservation education has an effect on students' environ-mental sensitivity to coral reefs. This influence is caused by the learning process carried out by students in observing and analyzing the conditions of their surroundings that can affect the survival of coral reefs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study by Puspitaningrum et al (2018) concluded that coral reef conservation education has an effect on students' environ-mental sensitivity to coral reefs. This influence is caused by the learning process carried out by students in observing and analyzing the conditions of their surroundings that can affect the survival of coral reefs.…”
Section: Resultsmentioning
confidence: 99%
“…One learning subject that can foster student environmental sensitivity is geography. Students can build environmental sensitivity through geography learning by maintaining awareness and preserving the environment (Puspitaningrum et al, 2018). Environmental sensitivity in learning geography in higher education requires students to understand, feel, and provide solutions to environmental problems (Kahraman, 2016;Cater, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Tentunya berdasarkan masalah tersebut guru diharapkan mampu menganalisis kebutuhan siswa yang disesuaikan dengan lingkungan dan kondisi siswa serta tujuan pembelajaran (Putri, 2021). Baik dalam menentukan metode atau bahkan media yang digunakan pada proses pembelajaran (Puspitaningrum et al, 2018). Salah satunya yang direkomendasikan beberapa peneliti terdahulu yaitu Problem Base Learning (Nur et al, 2016).…”
Section: Pendahuluanunclassified
“…Sustainability impacts are formed as two positive and negative sides (Kinseng et al, 2018). If viewed from the positive side, if there is a sense of concern for the local community and the government, it will have a positive impact on the existence of a coral reef conservation area (Roberts et al, 2012) which can be used as educational tourism for environmental conservation, especially in marine tourism (Puspitaningrum et al, 2018). However, there are negative impacts if it is not done with a caring attitude.…”
Section: Introductionmentioning
confidence: 99%